Human gingiva‐derived mesenchymal stem cells alleviate inflammatory bowel disease via IL‐10 signalling‐dependent modulation of immune cells. (8th July 2019) - Lu, Yousheng; Xu, Yueran; Zhang, Shaopeng; Gao, Ji; Gan, Xiaojie; Zheng, Ju; Lu, Ling; Zeng, Wenquan; Gu, Jian
Abstract: Current evidence indicates that inflammatory bowel disease (IBD) is caused primarily by impaired mucosal immunity, resulting in an imbalance between epithelial barrier function and tissue inflammation. Human gingiva‐derived mesenchymal stem cells (GMSCs) exhibit immunomodulatory and anti‐inflammatory effects in a variety of immunity‐ and inflammation‐associated diseases. However, the role of GMSCs in treating IBD has not been elucidated. Our study, therefore, examined the therapeutic effect and mechanism of GMSCs in a murine colitis model of IBD. Our results indicate that the infusion of GMSCs significantly prolonged survival and relieved symptoms. Phenotype analyses showed that the frequencies of NK1.1 + and CD11b + cells, as well as CD4 T cells in the spleen, were suppressed in GMSC‐treated mice compared with the PBS‐ or fibroblast‐treated control groups. Additionally, GMSC treatment markedly increased the numbers of interleukin (IL)‐10 + regulatory T cells, reduced the secretion of pro‐inflammatory cytokines, and increased production of anti‐inflammatory cytokines. A mechanistic study revealed that anti‐IL‐10R antibody abolished the protective effect of GMSCs compared with mice treated with anti‐IgG antibody. Thus, our results indicate that GMSCs play a critical role in alleviating colitis by modulating inflammatory immune cells via IL‐10 signalling.